SEO timing and liquidity risk - Lin, Ji-Chai; Wu, YiLin (Journal of Corporate Finance, 2013)
We extend the market timing literature to show that SEO timing can be characterized by the dynamics of liquidity risk. That is, firms tend to issue SEOs when liquidity risk declines to the point where investors have least concern of the risk. In the absence of liquidity risk, market risk rises right before SEOs and then gradually falls afterwards, consistent with the Q-theory (Carlson et al., 2010). However, once we include liquidity risk factor into the model for expected returns, issuing firms' market risk behaves like that of matched non-issuers, suggesting an omitted risk factor problem in SEO studies that does not take into account the effect of liquidity risk on stock returns. Furthermore, there is no evidence of post-issue long-run underperformance. Our results imply that, instead of timing alpha (i.e., exploiting overpricing, as behavioral finance has suggested), issuing firms time liquidity beta to minimize their cost of equity capital. The liquidity beta timing is especially evident in large offer size issuers.